1993
DOI: 10.1128/mcb.13.9.5702
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulator Leu3 of Saccharomyces cerevisiae: separation of activator and repressor functions.

Abstract: The Leu3 protein of Saccharomyces cerevisiae binds to specific DNA sequences present in the 5' noncoding region of at least five RNA polymerase II-transcribed genes. Leu3 (26). Third, in the absence of a-IPM, Leu3p acts as a repressor of transcription (5,26). Leu3p thus appears to be a molecular on-off switch, where "off" means not just the absence of activation, but actual suppression of transcription below basal levels.Three major functions of the 886-residue-long Leu3p (DNA binding, transcriptional activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 31 publications
(33 reference statements)
2
38
0
Order By: Relevance
“…To substantiate further the idea that Leu3p is modulated in a mammalian environment in a fashion similar to what had been seen in yeast, we performed in vitro transcription assays using nuclear extract from untransfected 30A5 cells and Leu3p that had been purified to near homogeneity from yeast cells overproducing the protein [26]. Extract was incubated with a template that contained the Ad2-ML promoter followed by a G-free cassette (Fig.…”
Section: Negative and Positive Effects Of Leu3p In A Mammalian Cell Nmentioning
confidence: 87%
See 1 more Smart Citation
“…To substantiate further the idea that Leu3p is modulated in a mammalian environment in a fashion similar to what had been seen in yeast, we performed in vitro transcription assays using nuclear extract from untransfected 30A5 cells and Leu3p that had been purified to near homogeneity from yeast cells overproducing the protein [26]. Extract was incubated with a template that contained the Ad2-ML promoter followed by a G-free cassette (Fig.…”
Section: Negative and Positive Effects Of Leu3p In A Mammalian Cell Nmentioning
confidence: 87%
“…The antibodies used were prepared against a chimeric protein that contained the 28 Cterminal amino acid residues of Leu3p fused to key limpet hemocyanin [26]. Immunoblotting was performed following existing protocols (Amersham International Life Science).…”
Section: Sds-polyacrylamide Gel Electrophoresis and Immunoblottingmentioning
confidence: 99%
“…Leu3p-In a previous paper, we initiated an analysis aimed at identifying residues of Leu3p that were important for AD masking (10). Since available evidence indicated that neither the extended DNA binding domain (DB, residues 1-173) nor a region adjacent to the AD (residues 774 -854) were required for modulation of Leu3p, whereas deletion of residues 174 -773 abolished modulation (9,11,20, and this paper), the analysis focused on the "middle region" (MR, residues 174 -773). Starting with a slow growing strain that contained a mutant Leu3p whose AD was permanently masked (Leu3p (D872N/D874N), designated Leu3-dd), faster growing suppressors were isolated following mutagenic PCR of the entire MR.…”
Section: Methodsmentioning
confidence: 99%
“…"Masking-unmasking" describes an equilibrium between inactive and active conformations of Leu3p that is influenced by ␣-IPM. "Repression" refers to a negative effect by Leu3p on transcription that requires neither the MR nor the AD of Leu3p (20). It may involve a separate negative factor (27).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation